ChemInform Abstract: Efficient Three‐Step Synthesis of Benzo[e]imidazo[1, 2‐c][1, 2, 3]triazines. Issue 34 (4th August 2016) - Pilali, Hedieh; Kamazani, Shirin Faraji; Moradi, Shahram; Moghimi, Setareh; Mahdavi, Mohammad; Firoozpour, Loghman; Shafiee, Abbas; Foroumadi, Alireza
Abstract: Title compounds (II) are efficiently synthesized through intermediate diazonium formation followed by intramolecular N—N bond formation using a simple and metal‐free strategy.